GAMBARAN HISTOPATOLOGIK PARU PADA HEWAN COBA POSTMORTEM - Ali, Sekar N.; Wangko, Sunny; Kalangi, Sonny J.R. (Universitas Sam Ratulangi, 2018)
Abstract: Postmortem changes play an important role in estimation of the time of death. This study was aimed to obtain the histopathological changes of lungs at several time intervals postmortem. This was a descriptive observational study using a local pig as the animal model killed by stabbing in the heart. Lung samples were taken at 15 minutes, 30 minutes, 45 minutes, 60 minutes, 75 minutes, 90 minutes, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 12 hours, and 24 hours postmortem. The results showed that the earliest histological change could be identified at 60 minutes postmortem in the form of alveolar dilatation. At 2 hours postmortem, congestion of smooth muscle layers of bronchioles was observed. The epithelial cells of the alveoli were undetected at 3 hours postmortem meanwhile the smooth muscle layers were undetected at 12 hours postmortem. At 24 hours postmortem, the bronchioles were still detected but the structure of their layers could not be identified. Conclusion: Histopathological changes were observed as alveolar dilatation at 60 minutes postmortem, followed by congestion of muscle layers, and undetected epithelial alveolar cells as well as smooth muscle layers. At 24 hours postmortem, bronchioles were still detected but the structure of their layers could not be identified.Keywords: histological changes, lungs, postmorterm Abstrak: Perubahan postmortem berperan penting untuk memperkirakan waktu kematian. Penelitian ini bertujuan untuk mendapatkan perubahan histopatologik paru hewan coba postmortem pada beberapa interval waktu. Jenis penelitian ialah deskriptif-observasional menggunakan hewan coba satu ekor babi lokal yang dimatikan dengan tikaman pada jantung. Sampel paru diambil dalam waktu 15 menit, 30 menit, 45 menit, 60 menit, 75 menit, 90 menit, 2 jam, 3 jam, 4 jam, 5 jam, 6 jam, 12 jam dan 24 jam postmortem. Hasil penelitian mendapatkan pada 60 menit postmortem terjadi dilatasi alveoli. Pada 2 jam postmortem tampak kongesti lapisan otot polos. Pada 3 jam postmortem sel-sel epitel alveoli tidak tampak lagi dan pada 12 jam postmortem lapisan otot polos tidak terdeteksi. Pada 24 jam postmortem bronkiolus masih dapat dideteksi tetapi struktur lapisannya tidak teridentifikasi. Simpulan: Perubahan awal histopatologik paru babi postmotem ini dimulai pada 60 menit postmortem berupa dilatasi alveoli, diikuti kongesti lapisan otot polos, serta tidak terdeteksinya sel-sel epitel alveoli dan lapisan otot polos. Pada 24 jam postmortem bronkiolus masih terdeteksi tetapi struktur lapisannya tidak teridentifikasi lagi.Kata kunci: perubahan histologik, paru, postmortem